2012
DOI: 10.1111/1574-6968.12012
|View full text |Cite
|
Sign up to set email alerts
|

Functional analyses of individual mating-type transcripts atMATloci inFusarium graminearumandFusarium asiaticum

Abstract: Members of the Fusarium graminearum species (Fg) complex, which are homothallic ascomycetous species, carry two opposite mating-type (MAT) loci in a single nucleus for controlling sexual development. We investigated the roles of three (MAT1-1-1, MAT1-1-2, and MAT1-1-3) and two (MAT1-2-1 and MAT1-2-3) transcripts located at both loci in representative Fg complex species (F. graminearum and Fusarium asiaticum). In self-fertile F. graminearum strains, the transcript levels of MAT1-1-1, MAT1-2-1, and MAT1-2-3 peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 34 publications
(50 reference statements)
5
50
1
Order By: Relevance
“…acridum (MAT1-2) 19 , which are heterothallic and possess only a single mating-type locus. Similar to the well-known homothallic plant pathogen Fusarium graminearum 34 , the organization of these two MAT loci in O . sinensis revealed the fusion status within the idiomorphic genomic region, which was particularly enriched in LTR retrotransponsons.…”
Section: Resultsmentioning
confidence: 92%
“…acridum (MAT1-2) 19 , which are heterothallic and possess only a single mating-type locus. Similar to the well-known homothallic plant pathogen Fusarium graminearum 34 , the organization of these two MAT loci in O . sinensis revealed the fusion status within the idiomorphic genomic region, which was particularly enriched in LTR retrotransponsons.…”
Section: Resultsmentioning
confidence: 92%
“…At this time, extensive comparisons between NIV and DON strains have been performed for genes controlling trichothecene production and sexual reproduction, such as those located at the mating type ( MAT ) loci (Kim et al, 2012) and trichothecene gene clusters (Kimura et al, 2003; Lee et al, 2001). These studies have revealed more than 80% nucleotide similarity between the two chemotype strains.…”
mentioning
confidence: 99%
“…As described above, nucleotide polymorphisms of TRI13 and TRI7 are known to determine trichothecene chemotypes of F. graminearum and F. asiaticum (Lee et al, 2001; Lee et al, 2002). Alterations in individual MAT gene expression is thought to be due to variations in self-fertility between two chemotype strains; the majority of NIV-producing F. asiaticum showed a lower self-fertility than the highly fertile DON-producing F. graminearum strains (Kim et al, 2012; Lee et al, 2009, 2012). At this time, genome sequencing of a Korean F. asiaticum strain is almost complete, which will allow comparisons to be made at the whole genome level (Yun et al, unpublished data).…”
mentioning
confidence: 99%
“…qRT-PCR analysis confirmed that the transcript levels of two MAT genes ( MAT1-1-1 and MAT1-2-1 , both of which are required for early sexual stage development in F. graminearum [39]), were elevated ∼2–3-fold in the Δ FgLaeA strain compared to the WT strain 24 h after perithecial induction on carrot agar (Fig. 3B); no changes were observed in the OE and add-back strains during the same time points for perithecial induction compared to those in WT (Fig.…”
Section: Resultsmentioning
confidence: 73%